Retrospective study of cancer patients’ predictive factors of care in a large, Hungarian tertiary care centre - Csaba Varga; János Girán; Eva Szabo; Márton Koch; Viktor Soós; Lilla Prenek; Lili Porcsa; Szabolcs Bellyei; Kyra Girán; István Kiss; Éva Pozsgai (BMJ Open, 2023)
Objectives To identify predictive factors of multiple emergency department (ED) visits, hospitalisation and potentially preventable ED visits made by patients with cancer in a Hungarian tertiary care centre.Design Observational, retrospective study.Setting A large, public tertiary hospital, in Somogy County, Hungary, with a level 3 emergency and trauma centre and a dedicated cancer centre.Participants Patients above 18 years with a cancer diagnosis (International Classification of Diseases, 10th Revision codes of C0000–C9670) who visited the ED in 2018, who had received their diagnosis of cancer within 5 years of their first ED visit in 2018 or received their diagnosis of cancer latest within the study year. Cases diagnosed with cancer at the ED (new cancer diagnosis-related ED visits) were also included, constituting 7.9% of visits.Primary outcome measures Demographic and clinical characteristics were collected and the predictors of multiple (≥2) ED visits within the study year, admission to inpatient care following the ED visit (hospitalisation), potentially preventable ED visits and death within 36 months were determined.Results 2383 ED visits made by 1512 patients with cancer were registered. Predictive factors of multiple (≥2) ED visits were residing in a nursing home (OR 3.09, 95% CI 1.88 to 5.07) and prior hospice care (OR 1.87, 95% CI 1.05 to 3.31). Predictive factors for hospitalisation following an ED visit included a new cancer diagnosis-related visit (OR 1.86, 95% CI 1.30 to 2.66) and complaint of dyspnoea (OR 1.61, 95% CI 1.22 to 2.12).Conclusions Being a resident of a nursing home and receiving prior hospice care significantly increased the odds of multiple ED visits, while new cancer-related ED visits independently increased the odds of hospitalisation of patients with cancer. This is the first study to report these associations from a Central-Eastern European country. Our study may shed light on the specific challenges of EDs in general and particularly faced by countries in the region.